Sosialisasi From Waste To Food Bersama Komunitas Wahana Usaha Jaya - Deasy Silvya Sari; Arry Bainus; Dina Yulianti; Savitry aditiany (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Food waste can be a threat to human life, both in terms of health and the environment. Food waste needs to be separated from other waste and can be processed into compost. This article aims to explain how to process food waste into compost and also use it for plant cultivation that can even be done at home. The method used in this service activity is socialization. The results of this activity show that students as participants in this activity are able to understand the urgency and how to process food waste into compost, and plant cultivation with compost which is shown by the making of several documentary videos of this activity.